Advancing Material Research in Indonesia: Insights from Computational Bibliometric Analysis - Kurniawan, Tedi; Nandiyanto, Asep Bayu Dani (Universitas Komputer Indonesia, 2023)
Material research in Indonesia has become a critical area of focus, driving advancements across various industries, including energy, electronics, and environmental sustainability. This study employs computational bibliometric analysis to assess the trends, contributions, and evolution of material research in Indonesia over the past two decades. By analyzing publication outputs, citation patterns, and key subject areas, this research offers a comprehensive overview of the state of material science in the country. The findings reveal a steady increase in research activity, with notable contributions from fields such as materials science, engineering, and environmental science. The paper also highlights key research themes and identifies opportunities for further growth, emphasizing the need for enhanced collaboration among academic, industrial, and governmental sectors to accelerate innovation in materials research.